2021
DOI: 10.1038/s41598-021-99140-z
|View full text |Cite|
|
Sign up to set email alerts
|

Dysregulated non-coding telomerase RNA component and associated exonuclease XRN1 in leucocytes from women developing preeclampsia-possible link to enhanced senescence

Abstract: Senescence in placenta/fetal membranes is a normal phenomenon linked to term parturition. However, excessive senescence which may be induced by telomere attrition, has been associated with preeclampsia (PE). We hypothesized that the telomerase complex in peripheral blood mononuclear cells (PBMC) and circulating telomere associated senescence markers would be dysregulated in women with PE. We measured long non-coding (nc) RNA telomerase RNA component (TERC) and RNAs involved in the maturation of TERC in PBMC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A recent review revealed clear associations between relative telomere length/integrity and male/female fertility factors (Vasilopoulos et al 2019). In this review, we have identified any additional clinical investigations since the Vasilopoulos paper and characterized them in the same manner as previously reported (Darmishonnejad et al 2019, Santana et al 2019, Tahamtan et al 2019, Berneau et al 2020, Huang et al 2020, Laurentino et al 2020, Pedroso et al 2020, Weeg et al 2020, Amirzadegan et al 2021, Berby et al 2021, Gentiluomo et al 2021, Lekva et al 2021, M'kacher et al 2021, Purdue-Smithe et al 2021, Rocca et al 2021, Lara-Cerrillo et al 2022, Michaeli et al 2022, Piani et al 2022. A visualization of the associations of relative telomere length with known male/female fertility factors from all aforementioned clinical investigations can be found in Fig.…”
Section: Telomere Integrity and Fertility Outcomesmentioning
confidence: 89%
“…A recent review revealed clear associations between relative telomere length/integrity and male/female fertility factors (Vasilopoulos et al 2019). In this review, we have identified any additional clinical investigations since the Vasilopoulos paper and characterized them in the same manner as previously reported (Darmishonnejad et al 2019, Santana et al 2019, Tahamtan et al 2019, Berneau et al 2020, Huang et al 2020, Laurentino et al 2020, Pedroso et al 2020, Weeg et al 2020, Amirzadegan et al 2021, Berby et al 2021, Gentiluomo et al 2021, Lekva et al 2021, M'kacher et al 2021, Purdue-Smithe et al 2021, Rocca et al 2021, Lara-Cerrillo et al 2022, Michaeli et al 2022, Piani et al 2022. A visualization of the associations of relative telomere length with known male/female fertility factors from all aforementioned clinical investigations can be found in Fig.…”
Section: Telomere Integrity and Fertility Outcomesmentioning
confidence: 89%
“…20 At the molecular level, the microRNA spectrum of blood exosomes has been used to evaluate the pathophysiology of preeclampsia and predict the disease, 21 and there are more and more studies at gene level. [22][23][24][25] Zhang and Horvath 26 conducted the first WGCNA analysis in 2005 and then published WGCNA R software package in R based on theory of the research method in 2008. As an efficient and accurate bioinformatics approach, WGCNA has been widely used for the gene network analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, additional exclusion criteria included gestational diabetes mellitus. A substudy [27] including 215 normotensive controls and 38 PE women were included in this study, and women developing gestational diabetes were excluded to reduce the heterogeneity in the control group. In the ACUTE-PE study, there were 34 PE and 61 control subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Deconvolution of cell-type proportions from the previous microarray data [27] was performed with CIBERSORTx using the validated LM22 signa-ture as Ref. [30].…”
Section: Cibersort Analysismentioning
confidence: 99%